The Impact of Immunosenescence on Pulmonary Disease - Michelle A. Murray; Sanjay H. Chotirmall (Mediators of Inflammation)
The global population is aging with significant gains in life expectancy particularly in the developed world. Consequently, greater focus on understanding the processes that underlie physiological aging has occurred. Key facets of advancing age include genomic instability, telomere shortening, epigenetic changes, and declines in immune function termed immunosenescence. Immunosenescence and its associated chronic low grade systemic “inflamm-aging” contribute to the development and progression of pulmonary disease in older individuals. These physiological processes predispose to pulmonary infection and confer specific and unique clinical phenotypes observed in chronic respiratory disease including late-onset asthma, chronic obstructive pulmonary disease, and pulmonary fibrosis. Emerging concepts of the gut and airway microbiome further complicate the interrelationship between host and microorganism particularly from an immunological perspective and especially so in the setting of immunosenescence. This review focuses on our current understanding of the aging process, immunosenescence, and how it can potentially impact on various pulmonary diseases and the human microbiome.